Etos Kerja Dalam Islam - Kirom, Cihwanul (TAWAZUN: Journal of Sharia Economic Law, 2018)
The meaning of "ethos" comes from Greek (ethos) which means character or character. Overall, the notion of ethos includes characteristics and attitudes, habits and beliefs, and so on, which are specific about an individual or group of people. From the words "ethos" will appear the words "ethics" and "ethical" which refer to the meaning of "morality / behavior" or are "morality", namely the essential quality of a person or a group, including a group of nations. It is also said that "ethos" means the distinctive soul of a group of people, which from that distinctive soul will develop the nation's view of good and bad, that is, its ethics.Ahmad Janan Asifudin, citing In the Hand Book of Term Psycology stated that ethos is interpreted as a distinctive view of a social group, a value system that lies behind the customs and procedures of a community. Whereas, Taufiq Abdullah defines it as an evaluative aspect which is a self-assessment of work originating from self-identity which is a sacred value that is the religious spiritual reality that he believes.Whereas the difference between ethos and ethics. The term ethics, theoretically can be divided into two senses. First, ethics comes from the Greek word ethos which means custom (character). In this sense, ethics is related to good life habits, both in oneself and in a society or community group that is passed on from one person to another or from one generation to another.The definition of work, as in the Big Dictionary of Indonesian Language is interpreted as an activity of doing something. El-Qussy as quoted by Ahmad Janan Asifuddin argues that human activities or actions are of two types. First, actions that are related to mental activities, and both actions are done accidentally. The first type has a characteristic of interest, namely to achieve the purpose or realize certain goals. While the second type is a random movement as seen in small baby movements that appear irregular, reflection movements and other movements that occur without the will of the will or thought process.Tata tasmara in his work ethic of a Muslim has an ethos formulation as follows In the form of axioms, Toto summarizes them in the form of a formula: KHI = T, US (M, A, R, A), KHI = Islamic Quality of Life, T = Tawhid, US = Charity piety, M = Motivation, A = Direction of Goals (Aim and Goal / Objectives), R = Taste and Ratio (Thinking and Recitation), A = Action, Actualization.